Heavy Metals in Marine Surface Sediments of Daya Bay, Southern China: Spatial Distribution, Sources Apportionment, and Ecological Risk Assessment - Wang, Huijuan; Fan, Zhengqiu; Kuang, Zexing; Yuan, Yuan; Liu, Huaxue; Huang, Honghui (Frontiers in Environmental Science, 2021)
Daya Bay, especially in the northwestern region, which is a nature reserve with larval economic fish and shrimp populations, is no longer an unpolluted marine environment due to the recent increases in anthropogenic activities. This study collected seasonal surface sediment samples from 20 sites in northwestern Daya Bay to evaluate pollution and ecological risks and to identify possible sources and transport pathways of heavy metals (Cd, Pb, Cr, Cu, Zn, Hg, As). The results showed that all the heavy metal concentrations were below the established primary standard criteria, except for concentrations of Cr in spring, as well as Cu and Zn in autumn at several sampling stations, which had excess rates of 35, 4.76, and 4.76%, respectively. The geoaccumulation index (Igeo) values of heavy metals indicated that all sites had unpolluted to moderate pollution levels. In comparison to the samples collected in autumn, those in spring experienced a higher degree of pollution, particularly Cr and As. The ecological risk indices of heavy metals in sediments ranged from 225.86 to 734.20 in spring and from 196.69 to 567.52 in autumn, suggesting that most sites had a moderate ecological risk or a considerable ecological risk, and very few a had high ecological risk. Moreover, ArcGIS10.2 software was used to visualize their spatial distribution, and the results were similar in both spring and autumn. The results of the Pearson correlation analysis and principal component analysis showed that Cu, Hg, and Pb might be affected by anthropogenic activities, and As might be derived from natural sources such as atmospheric inputs. A cluster analysis showed that heavy metals were mainly affected by the negative impacts of human beings on the environment.